Clinical and epidemiological aspects related to the detection of adenovirus or respiratory syncytial virus in infants hospitalized for acute lower respiratory tract infection - Eduardo A. Ferone; Eitan N. Berezin; Giuliana S. Durigon; Cristiane Finelli; Maria C.C. Felício; Juliana G. Storni; Edison L. Durigon; Danielle B. L. de Oliveira (Elsevier, 2014)
Objective: to characterize and compare clinical, epidemiological, and laboratory aspects of infants with acute lower respiratory infection (ALRI) associated with the detection of adenovirus (ADV) or respiratory syncytial virus (RSV). Methods: a preliminary respiratory infection surveillance study collected samples of nasopharyngeal aspirate (NPA) for viral research, linked to the completion of a standard protocol, from children younger than two years admitted to a university hospital with ALRI, between March of 2008 and August of 2011. Polymerase chain reaction (PCR) was used for eight viruses: ADV, RSV, metapneumovirus, Parainfluenza 1, 2, and 3, and Influenza A and B. Cases with NPA collected during the first 24 hours of admission, negative results of blood culture, and exclusive detection of ADV (Gadv group) or RSV (Grsv group) were selected for comparisons. Results: the preliminary study included collection of 1,121 samples of NPA, 813 collected in the first 24 hours of admission, of which 50.3% were positive for at least one virus; RSV was identified in 27.3% of cases surveyed, and ADV was identified in 15.8%. Among the aspects analyzed in the Gadv (n = 58) and Grsv (n = 134) groups, the following are noteworthy: the higher mean age, more frequent prescription of antibiotics, and the highest median of total white blood cell count and C-reactive protein values in Gadv. Conclusions: PCR can detect persistent/latent forms of ADV, an aspect to be considered when interpreting results. Additional studies with quantitative diagnostic techniques could elucidate the importance of the high frequency observed. Resumo: Objetivo: caracterizar e comparar aspectos clínicos, epidemiológicos e laboratoriais de lactentes com evidências de infecção aguda do trato respiratório inferior (IATRI) associada à detecção do adenovírus (ADV) ou do vírus sincicial respiratório (VSR). Métodos: um estudo preliminar de vigilância de infecções respiratórias desenvolveu coleta de aspirado nasofaríngeo (ANF) para pesquisa viral, vinculada ao preenchimento de protocolo padrão, de menores de dois anos internados com quadro de IATRI em hospital universitário, entre março de 2008 e agosto de 2011. Utilizou-se técnica da reação em cadeia da polimerase (PCR) para oito vírus: ADV, VSR, metapneumovírus, parainfluenza 1, 2 e 3 e influenza A e B. Foram selecionados para comparações os casos com ANF coletado nas primeiras 24horas da admissão, resultado de hemocultura negativo e detecção exclusiva de ADV (grupo Gadv) ou VSR (grupo Gvsr). Resultados: o estudo preliminar incluiu coleta de 1.121 amostras de ANF, sendo 813 coletadas nas primeiras 24 h da admissão, das quais 50,3% foram positivas para ao menos um dos vírus, com VSR em primeiro lugar, em 27,3%, e ADV em segundo, em 15,8% dos casos pesquisados. Dentre os aspectos analisados nos grupos Gadv (n=58) e Gvsr (n=134), destacaram-se a média da idade mais elevada, maior frequência da prescrição de antibióticos e medianas mais elevadas para contagem total de leucócitos e valores da proteína C-reativa no Gadv. Conclusões: a PCR utilizada pode detectar formas persistentes/latentes de ADV, aspecto a ser considerado ao interpretar os resultados. Estudos complementares com técnicas diagnósticas quantitativas, por exemplo, poderiam evidenciar a importância da elevada frequência verificada. Keywords: Respiratory tract infections, Adenoviruses human, Child hospitalized, Palavras-chave: Infecções respiratórias, Adenovírus humanos, Criança hospitalizada